Anomalous Readings Mentioned by Imam al-Samarqandi (d. 375 AH) in His Tafsir "Bahr al- Ulum" in Surahs al-Baqarah, al-An am, and al-A raf: A Compilation and Study - Musa Ṭaha Ṣayyah, (Islamic Sciences Journal, 2025)
ABSTRACT The science of Qur anic readings ( ilm al-qira at) is among the most significant disciplines due to its direct connection with the Glorious Qur’an. The history of these readings traces back to the revelation bestowed upon our Prophet Muhammad (peace be upon him), which was revealed in seven modes (ahruf) to facilitate comprehension for the Ummah. The Companions (may Allah be pleased with them) received these readings, which were then transmitted through the Successors and subsequent generations until they reached the Ten Canonical Reciters (al-Qurra al- Asharah). Among these readings are those that are mass-transmitted (mutawatir) and those deemed anomalous (shadhdh). The latter constitutes the focus of this research, which examines the anomalous readings cited in the exegesis (tafsir) "Bahr al- Ulum" by Imam al-Samarqandi. The study underscores the significance of anomalous readings in elucidating additional exegetical meanings